2015
DOI: 10.1063/1.4928171
|View full text |Cite
|
Sign up to set email alerts
|

The influence of MoOx gap states on hole injection from aluminum doped zinc oxide with nanoscale MoOx surface layer anodes for organic light emitting diodes

Abstract: The effective workfunction of Al doped ZnO films (AZO) increased from 4.1 eV to 5.55 eV after surface modification with nanoscale molybdenum sub-oxides (MoOx). Hole only devices with anodes consisting of 3 nm of MoOx on AZO exhibited a lower turn-on voltage (1.5 vs 1.8 V), and larger charge injection (190 vs 118 mA/cm2) at the reference voltage, compared to indium tin oxide (ITO). AZO devices with 10 nm of MoOx exhibited the highest workfunction but performed poorly compared to devices with 3 nm of MoOx, or st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Oxygen loss during MoO x deposition results in oxygen vacancies leading to the oxidation transitions in Mo and to generation of gap states by partial filling of the unoccupied 4d orbitals of molybdenum atoms . G 1 is associated with singly occupied Mo 4d orbitals, while G 2 feature is associated with doubly occupied Mo 4d orbitals . Previous works have already reported that gap states can be induced by interaction between MoO x layer and inorganic substrates or organic molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Oxygen loss during MoO x deposition results in oxygen vacancies leading to the oxidation transitions in Mo and to generation of gap states by partial filling of the unoccupied 4d orbitals of molybdenum atoms . G 1 is associated with singly occupied Mo 4d orbitals, while G 2 feature is associated with doubly occupied Mo 4d orbitals . Previous works have already reported that gap states can be induced by interaction between MoO x layer and inorganic substrates or organic molecules .…”
Section: Resultsmentioning
confidence: 99%
“…Li et al increased the WF of a Ga-doped ZnO (GZO) thin film from 3.29 to 4.87 eV through surface modification with a phosphonic acid of F 5 PPA; however, it has not been applied to any devices, and its effect on a device is still unknown. Finally, Jha et al proposed the surface modification of AZO with physisorption of transition-metal oxides (e.g., MoO 3– x , WO 3– x , or V 2 O 5– x ) and initially applied them to OLEDs to improve the hole injection efficiency. Although a WF of 5.55 eV was achieved by utilizing the high WF characteristic of MoO 3– x , the large resistivity (10 5 to 10 6 Ω·cm) of MoO 3– x significantly increased the series resistance of OLEDs, resulting in an increase of ca. 30% in the threshold voltage .…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Jha et al proposed the surface modification of AZO with physisorption of transition-metal oxides (e.g., MoO 3– x , WO 3– x , or V 2 O 5– x ) and initially applied them to OLEDs to improve the hole injection efficiency. Although a WF of 5.55 eV was achieved by utilizing the high WF characteristic of MoO 3– x , the large resistivity (10 5 to 10 6 Ω·cm) of MoO 3– x significantly increased the series resistance of OLEDs, resulting in an increase of ca. 30% in the threshold voltage . This indicates that the high-resistance MoO 3– x modifier increases the surface WF of AZO at the cost of increasing the series resistance of the device, resulting in the deterioration of the device performance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation